Analisis Kesesuaian Nilai Profil Pelajar Pancasila Pada Soal Uraian Buku Teks Bahasa Indonesia Kelas VIII Penerbit Intan Pariwara - Efrianti, Diajeng Susila; Hidayah, Rizqi Nur (Prawara: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
This research aims to determine the suitability of the Pancasila Student Profile value in the description of the class VIII Indonesian language textbook published by Intan Pariwara. This research is descriptive qualitative in nature. The data source in this research is the Class VIII Indonesian language textbook published by Intan Pariwara. The data in this research is about descriptions labeled Hots. The data collection techniques used in this research are notetaking and documentation. This research produced 25 data including the dimension of faith, there is 1 data, there are 2 data for diversity, there are 4 data for mutual cooperation, there are 9 data for independence, there are 9 data for creativity, and there are 9 data for critical thinking. Of these six dimensions, there are questions in the form of hots and lots. From several data findings, there were only 3 dimensions or profiles of Pancasila students that were most dominant, namely independent, creative and critical reasoning. In the independent dimension, students are asked to express their opinions, in the creative dimension, students are asked to make advertisements as creative as possible, and in the critical reasoning dimension, students are asked to find language errors and then correct them.